Penguatan Memahami Kitab Nurul Yaqin Dengan Media Gambar dan Peta - M. Yusuf (Universitas Islam Lamongan, 2020)
The Nurul Yaqin book is one of the yellow books that tell the history of the journey and struggle of the Prophet Muhammad SAW in spreading Islam. In the book, many stories are told about the joys and sorrows of the Prophet and his companions in the mission of spreading Islam. There are also many descriptions of essential and historical events that have become the treasures of Muslims. One of the efforts to connect the chain of the Prophet's struggle is to teach this book again with methods and media that are fun to students. The use of instructional media is expected to help students capture their imagination, increase their enthusiasm, spark their enthusiasm and provoke their creativity in studying historical books. This research is library research with a qualitative research approach. The data collection method uses the documentary study method. The data analysis method used is the content analysis method. The purpose of this study is to help teachers make it easier for students to accept and understand the contents of the Nurul Yaqin book by utilizing learning media in the form of pictures and maps.